2010
DOI: 10.1111/j.1755-3768.2008.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of 345 eye amputations carried out in the period 1996–2003, at Rigshospitalet, Denmark

Abstract: ABSTRACT.Purpose: The aim of this study was to identify the number of eye amputations, and the causative diagnoses, indications for surgery and surgical techniques applied, and to evaluate a possible change in surgical technique in a tertiary referral centre in Denmark. Methods: The hospital database was screened using surgery codes for patients who had undergone bulbar evisceration, enucleation or orbital exenteration in the period 1996-2003. Patient records were reviewed for gender, age, time since surgery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 9 publications
(17 reference statements)
4
41
0
2
Order By: Relevance
“…Of the 39 patients with pain, 27 (70%) were treated with an evisceration and 12 (30%) with an enucleation in the time period . Among the entire group of EA patients in the same period, 43% were eviscerated, 52% were enucleated, and 5% had an orbital exenteration (Rasmussen et al 2010).…”
Section: Triggers and Relievers Of Phantom Painmentioning
confidence: 97%
“…Of the 39 patients with pain, 27 (70%) were treated with an evisceration and 12 (30%) with an enucleation in the time period . Among the entire group of EA patients in the same period, 43% were eviscerated, 52% were enucleated, and 5% had an orbital exenteration (Rasmussen et al 2010).…”
Section: Triggers and Relievers Of Phantom Painmentioning
confidence: 97%
“…Twothirds of the patients in this study were men, which is the same as in the previous study even though the number of cases was almost fourfold in that study, and the time period of the study was more than twice as long. Other studies have also reported male predominance, 51-71% (Erie et al 1992;de Gottrau et al 1994;Gu¨nalp et al 1997;Hansen et al 1999;Custer & Reistad 2000;Vemuganti et al 2001;Kitzmann et al 2003;Bal et al 2007;Rasmussen et al 2010).…”
Section: Age-groups (Years)mentioning
confidence: 99%
“…Other studies have reported median age of enucleation of 46 years (Erie et al 1992), 53 years (Rasmussen et al 2010) and of 60 years (Kitzmann et al 2003). Some studies have only reported the mean age, for example, de Gottrau et al (1994) of 57 years and Hansen et al (1999) of 59 years.…”
Section: Age-groups (Years)mentioning
confidence: 99%
See 1 more Smart Citation
“…Today, worldwide, the number of patients who have been formally indicated for these types of surgeries continues to be high (1,2) . Besides the feeling of loss of the eyeball, the evisceration or enucleation predisposes the individual to esthetic defects such as enophthalmos, deepening of the eyelid superior sulcus, ptosis, incomplete transference of movement to the prosthesis, reduction of the lower fornix, and flaccidity of the lower eyelid (3) .…”
Section: Introductionmentioning
confidence: 99%